2021
DOI: 10.1007/s43032-020-00450-w
|View full text |Cite
|
Sign up to set email alerts
|

Decreased circUBAP2 Expression Is Associated with Preeclampsia by Limiting Trophoblast Cell Proliferation and Migration

Abstract: Preeclampsia (PE) is a common obstetric disease and a major cause of maternal, newborn, and fetal death. This condition is a multisystem disorder characterized by hypertension, proteinuria, and involvement of the kidney, liver, and nervous system. It is generally believed that the placenta is the main cause of PE. circRNAs are a special class of noncoding RNAs that can form covalently closed continuous ring structures with tissue-specific conservation, and they have been reported to play a wide range of regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The impaired cell growth of trophoblast cells may contribute to the occurrence of PE [4,5]. The Ki67 is a cell proliferation marker, and the Ki67 expression is positively associated with cell cycle progression.…”
Section: Ki67 Is Reduced In Placenta From Pe Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impaired cell growth of trophoblast cells may contribute to the occurrence of PE [4,5]. The Ki67 is a cell proliferation marker, and the Ki67 expression is positively associated with cell cycle progression.…”
Section: Ki67 Is Reduced In Placenta From Pe Patientsmentioning
confidence: 99%
“…For normal placentation, the cytotrophoblasts derived from trophoblastic cells need to invade the spiral arteries [3]. The impairment of cell proliferation of trophoblastic cells may cause detrimental effects to the differentiation and invasion of cytotrophoblasts, promoting the development of PE [4,5]. Therefore, it is urgent to dis-cover the molecular mechanism engaged in the regulation of trophoblastic cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, circ_0003496 was less abundant in placental tissues and acted on the miR-1244/forkhead box M1 (FOXM1) axis to regulate PE progression. 10 This indicated that circ_0003496 might be a future molecular marker in the diagnostic and therapeutic process of PE. Further, dysregulation of circRNAs was also found in various types of inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of circRNAs have been identified to be dysregulated in various types of diseases. 9 , 10 , 11 , 12 In cancer, numerous circRNAs have been observed to be dysregulated. For instance, circRNA CDR1 antisense RNA (Cdr1as) was revealed to be abnormally upregulated in hepatocellular carcinoma (HCC) cells, and circRNA Cdr1as upregulation acting on the miR-1270/alpha fetoprotein (AFP) axis accelerated the proliferation and metastasis of hepatocellular carcinoma cells, which revealed that circRNA Cdr1as had the promise to become a molecular marker for HCC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed that circ_0003945 showed resistance to digestion by ribonuclease R (RNase R), whereas the corresponding linear transcript was considerable diminished after RNase R treatment, underscoring the stability of its covalently closed-loop structures ( 42 , 43 ). Circ_0003945 have been associated with a variety of diseases, including various neoplasms and non-malignant conditions such as microcirculatory perfusion ( 44 , 45 ), diabetic retinopathy (DR) ( 35 ), osteoarthritis (OA) ( 46 ), preeclampsia (PE) ( 47 ), and milk fat metabolism ( 48 ). Noteworthy, circ_0003945 was highly overexpressed and linked to poor prognosis, including in glioma ( 49 ), thyroid cancer (TC) ( 36 ), esophageal cancer (EC) ( 50 ), non-small cell lung cancer (NSCLC) ( 51 ), breast cancer (BC) ( 34 ), hepatocellular carcinoma (HCC) ( 52 ), pancreatic cancer ( 53 ), colorectal cancer (CRC) ( 54 ), ovarian cancer (OC) ( 55 ), cervical cancer (CC) ( 56 ), prostate cancer ( 57 ), and osteosarcoma ( 58 ) ( Figure 3 ).…”
Section: Introductionmentioning
confidence: 99%